Perspectives of an Enterprise Integration Plug-in System Architecture for Networked Manufacturing Systems - Ghannam, A. N.; Mansour, H.; El-Bastawissy, A.; Hamed, M. (Engineering, Technology & Applied Science Research, 2019)
This paper is a part of a research project funded by the Science and Technology Development Fund (STDF), to create a product serving the digital transformation of Egyptian manufacturing companies. It allows a manufacturing company to be a member of a distributed manufacturing network. The resulting system can be plugged into any ERP system. In this work, the limitation of a centralized integration entity to satisfy loosely coupling of distributed systems is overcome. The SOA framework and the remote method invocation (RMI) are applied using SOAP-XML technology. Enterprise integration patterns (EIP) were used in the architecture design.